Genetic engineering of a thermophilic acetogen, Moorella thermoacetica Y72, to enable acetoin production - Kato, Junya; Fujii, Tatsuya; Kato, Setsu; Wada, Keisuke; Watanabe, Masahiro; Nakamichi, Yusuke; Aoi, Yoshiteru; Morita, Tomotake; Murakami, Katsuji; Nakashimada, Yutaka (Frontiers in Bioengineering and Biotechnology, 2024)
Acetogens are among the key microorganisms involved in the bioproduction of commodity chemicals from diverse carbon resources, such as biomass and waste gas. Thermophilic acetogens are particularly attractive because fermentation at higher temperatures offers multiple advantages. However, the main target product is acetic acid. Therefore, it is necessary to reshape metabolism using genetic engineering to produce the desired chemicals with varied carbon lengths. Although such metabolic engineering has been hampered by the difficulty involved in genetic modification, a model thermophilic acetogen, M. thermoacetica ATCC 39073, is the case with a few successful cases of C2 and C3 compound production, other than acetate. This brief report attempts to expand the product spectrum to include C4 compounds by using strain Y72 of Moorella thermoacetica. Strain Y72 is a strain related to the type strain ATCC 39073 and has been reported to have a less stringent restriction-modification system, which could alleviate the cumbersome transformation process. A simplified procedure successfully introduced a key enzyme for acetoin (a C4 chemical) production, and the resulting strains produced acetoin from sugars and gaseous substrates. The culture profile revealed varied acetoin yields depending on the type of substrate and culture conditions, implying the need for further engineering in the future. Thus, the use of a user-friendly chassis could benefit the genetic engineering of M. thermoacetica.